Health Care Access, Costs, and Treatment Dynamics: Evidence from In Vitro Fertilization - Hamilton, Barton H.; Jungheim, Emily; McManus, Brian; Pantano, Juan (American Economic Review, 2018)
We study public policies designed to improve access and reduce costs for in vitro fertilization (IVF). High out-of-pocket prices can deter potential patients from IVF, while active patients have an incentive to risk costly high-order pregnancies to improve their odds of treatment success. We analyze IVF's rich choice structure by estimating a dynamic model of patients' choices within and across treatments. Policy simulations show that insurance mandates for treatment or hard limits on treatment aggressiveness can improve access or costs, but not both. Insurance plus price-based incentives against risky treatment, however, can together improve patient welfare and reduce medical costs.